Seed Dispersal and Frugivory: Ecology, Evolution and Conservation. Third International Symposium-Workshop on Frugivores and See 2002
DOI: 10.1079/9780851995250.0209
|View full text |Cite
|
Sign up to set email alerts
|

The role of seed size in dispersal by a scatter-hoarding rodent.

Abstract: A field experiment was conducted in the Nouragues Reserve, an undisturbed lowland rain forest in French Guiana, to test possible selective pressures towards higher seed value of Carapa procera by scatter-hoarders, and to quantify survival probabilities of seeds harvested and cached by red acouchies (Myoprocta exilis). The following hypotheses were also tested: (1) large seeds are more likely to be harvested by acouchies than small seeds; (2) large seeds are harvested by acouchies more quickly than small seeds;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
185
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(203 citation statements)
references
References 47 publications
14
185
3
1
Order By: Relevance
“…Also, many studies have found a positive relationship between dispersal distance and seed size (e.g. Hurly & Robertson 1987;Forget et al 1998;Jansen & Forget 2001;Jansen et al 2002, 2004, Vander Wall 2003this study). The above responses all make sense in terms of economy: seed scarcity in time or space increases the 'value-of-exchange' of seeds while seed size increases the 'value-of-use', which together determine the economic value of seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, many studies have found a positive relationship between dispersal distance and seed size (e.g. Hurly & Robertson 1987;Forget et al 1998;Jansen & Forget 2001;Jansen et al 2002, 2004, Vander Wall 2003this study). The above responses all make sense in terms of economy: seed scarcity in time or space increases the 'value-of-exchange' of seeds while seed size increases the 'value-of-use', which together determine the economic value of seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that scatter-hoarding rodents and birds tend to cache large, more nutritious seeds further away (and thus at lower densities) than small seeds (e.g. Bossema 1979;Hurly & Robertson 1987;Forget et al 1998;Jansen & Forget 2001;Jansen et al 2002Jansen et al , 2004Vander Wall 2003;Leaver 2004; but see Brewer 2001). Jansen et al (2004) argued that the value of food to hoarders is determined not only by the nutritional content (i.e.…”
mentioning
confidence: 99%
“…Larger nuts and seeds are usually carried greater distances to cache sites (Hallwachs 1986;Vander Wall 1995;Jansen et al 2002Jansen et al , 2004Xiao et al 2004Xiao et al , 2005aTakahashi et al 2007;Zhang et al 2008); however, a few studies (Brewer 2001;Xiao et al 2004) have failed to observe this behaviour. Large nuts also have longer residence times in caches ( Jansen et al 2002), and large nuts often demonstrate increased fitness ( Jansen et al 2004). For example, larger Quercus serrata acorns have longer cache lifetimes and are more likely to produce seedlings in spring (Xiao et al 2004); however, this was not true for larger acorns of Quercus liaotungensis .…”
Section: Size and Nutritional Content Of Propagulesmentioning
confidence: 99%
“…Both intra-and interspecifically, small seeds and nuts have a greater chance of being eaten while large seeds and nuts have a greater chance of being scatter hoarded (Forget et al 1998;Jansen et al 2002Jansen et al , 2004Xiao & Zhang 2006;Vander Wall 2008;Zhang et al 2008), although other nut traits (e.g. fat or tannin content) can alter this general pattern (Xiao & Zhang 2006;see below).…”
Section: Size and Nutritional Content Of Propagulesmentioning
confidence: 99%
“…We recorded the animal species and the exact time of seed removal for each seed (as in Jansen et al 2002Jansen et al , 2004Jansen & den Ouden 2005), and identified the individual if possible. Each seed plot was checked daily and removed seeds were located by sight or with hand-held radiotelemetry equipment (Yaesu-VR500, Cypress, CA, U.S.A.) to determine dispersal distance and seed fate.…”
Section: Seed Trackingmentioning
confidence: 99%